Candidate apoptotic and DNA repair gene approach confirms involvement of ERCC1, ERCC5, TP53 and MDM2 in radiation-induced toxicity in head and neck cancer. (April 2017) - Borchiellini, D.; Etienne-Grimaldi, M.C.; Bensadoun, R.J.; Benezery, K.; Dassonville, O.; Poissonnet, G.; Llorca, L.; Ebran, N.; Formento, P.; Château, Y.; Thariat, J.; Milano, G.
Highlights: The candidate-gene approach in HNSCC is relevant as few studies have investigated the topic. Radiation-induced toxicity is a crucial point in terms of efficacy and clinical sequelae. The association between SNPs and toxicity is discussed as regards the known functional significance of each SNP. Abstract: Introduction: Single nucleotide polymorphisms (SNPs) of DNA repair and apoptosis genes have been associated with outcome in head and neck squamous cell carcinoma (HNSCC) patients receiving radiotherapy (RT). Our goal was to conduct a candidate gene study in HNSCC patients receiving RT or chemoRT. Methods: 122 non-resectable HNSCC patients undergoing RT (N = 38) or chemoRT (N = 84) between 1992 and 2006 were retrospectively analyzed. ERCC1 Lys259Thr (rs735482), ERCC2 Lys751Gln (rs13181), ERCC5 His46His C > T (rs1047768), XRCC1 Arg399Gln (rs25487), TP53 Arg72Pro (rs1042522) and MDM2 309T > G (rs2279744) were analyzed on tumor DNA. SNP profile was considered to assess RT-related toxicity. Results: All 120 evaluable patients experienced RT-related toxicity at any time. Among them, 83% had G3-4 acute side-effects during RT, mainly dysphagia, mucositis, epithelitis and/or xerostomia (DMEX). 28/105 patients (27%) had early G3-4 toxicity up to 3 months after the end of RT. 29/96 patients (30%) had G3-4 late toxicity thereafter. The presence of G allele of MDM2 or Thr allele of ERCC1 was associated with a significantly higher risk of acute and/or early DMEX toxicity. The MDM2 309GG genotype was linked to a higher risk of acute G3-4 dermatitis. The ERCC5 TT genotype was associated with more frequent G3-4 late cervical skin fibrosis or xerostomia. Pro allele of TP53 72 was associated with a higher risk of G3-4 osteoradionecrosis. Conclusion: Relevant SNPs in DNA repair ( ERCC1 and ERCC5 ) and apoptosis ( MDM2 and TP53 ) genes might influence the severity of radiation-related side-effects in HNSCC patients. Prospective clinical SNP-based validation studies are needed on these bases.